2009
DOI: 10.4049/jimmunol.0802592
|View full text |Cite
|
Sign up to set email alerts
|

Improved Survival and Reduced Vascular Permeability by Eliminating or Blocking 12/15-Lipoxygenase in Mouse Models of Acute Lung Injury (ALI)

Abstract: Acute lung injury (ALI) is a prevalent disease associated with high mortality. 12/15-lipoxygenase (12/15-LO) is an enzyme producing 12-hydroxyeicosatetraenoic acid (HETE) and 15-HETE from arachidonic acid. To test whether 12/15-LO is involved in increasing vascular permeability in the lung, we investigated the role of 12/15-LO in murine models of LPS-induced pulmonary inflammation and clinically relevant acid-induced ALI. The vascular permeability increase upon LPS inhalation was abolished in Alox15−/− mice la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 62 publications
1
45
0
2
Order By: Relevance
“…Because many risk factors for cardiovascular diseases increase the expression or activity of 12/15-LO and atherosclerotic but not healthy arteries produce 15-HETE, we asked the question whether this lipid molecule alters endothelial barrier function promoting transmigration of monocytes, thereby setting the stage for atherogenesis. In this context, it should be noted that studies from other laboratories have reported that deletion of the 12/15-LO gene reduces vascular permeability in a mouse model of acute lung injury (25). In addition, a recent report showed that 12(S)-HETE by NADPH oxidase-dependent reactive oxygen species production and VEGF receptor-2 tyrosine phosphorylation increases retinal endothelial cell permeability (26).…”
mentioning
confidence: 99%
“…Because many risk factors for cardiovascular diseases increase the expression or activity of 12/15-LO and atherosclerotic but not healthy arteries produce 15-HETE, we asked the question whether this lipid molecule alters endothelial barrier function promoting transmigration of monocytes, thereby setting the stage for atherogenesis. In this context, it should be noted that studies from other laboratories have reported that deletion of the 12/15-LO gene reduces vascular permeability in a mouse model of acute lung injury (25). In addition, a recent report showed that 12(S)-HETE by NADPH oxidase-dependent reactive oxygen species production and VEGF receptor-2 tyrosine phosphorylation increases retinal endothelial cell permeability (26).…”
mentioning
confidence: 99%
“…4,41,42 These MPs are considered to be conveyers of inflammatory cytokines and other components such as microRNA and can interact with leukocytes. 42,43 Third, to assess arachidonic acid metabolism in platelets, we monitored the generation of the 12-lipoxygenase's product 12-hydroxyeicosatetraenoic acid (12-HETE), a bioactive lipid present in inflamed lungs [44][45][46] and induced by H 1 N 1 infection in mice. 47 Washed human platelets (.99.5% pure, supplemental Figure 2) were incubated in 2% human serum (HS) in the absence or presence of H 1 N 1 .…”
Section: Resultsmentioning
confidence: 99%
“…with 100 ml 1% Evans blue (SigmaAldrich), as described previously (22), and tumors were harvested 30 min after treatment. Evans blue was extracted from tumors with formamide (1 ml/sample) overnight at 56˚C.…”
Section: In Vivo Permeability Assaymentioning
confidence: 99%